Metafisika Cahaya Suhrawardi - Muhammad Sabri (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2010)
This article deals with the critique toward west philosophy in terms of the proportion of reason in gaining knowledge. It employs qualitative analysis on his research. The author initially collects documents and relevant materials in relation to the topic then analyze them. As stated in the article, the author believe that the Muslim thinkers tend to contend that west philosophy mainly focus on Aristotelian logic rather than the concept of Plato and Plotinus mystic. Suhrawardi, in this sense, is one of the Muslim philosophers is standing to support Plato’s idea. He, as contended by the author, further developed Plato’s idea into teosofi concept. Teosofi introduces a new approach which combines philosophical theory and peripatetic tradition through Sufism. The author come to conclude that Suhrawardi tend to see the truth can not be reached by the philosopher who solely employ the reason through philosophy or Sufism. Both need to be combined with teosofi concept as popularly discussed in his magnum opus, hikmat al-isyraq. Suhrawardi discussed the contrast between philosophy and Sufism in his book and offer solution which is further called teosofi.